Estudo das características morfológicas do lodo anammox em reatores alimentados com efluente da suinocultura - Cavaler, Jadiane Paola (2024)
Swine production is one of the leading agricultural chains in Brazil, and it has a significant economic and social impact. With the increase in global demand for animal protein, intensive production has become more common, providing greater productivity and strict sanitary control and generating large volumes of waste rich in ammoniacal nitrogen. Anaerobic digestion (AD) is widely used to treat this wastewater, but the digestate generated still has high concentrations of nitrogen, which requires additional processes to remove it efficiently. The anammox process and its variations, such as deammonification, have been investigated as effective alternatives for removing nitrogen from effluents with high ammonia loads. However, implementing these processes faces challenges, such as obtaining and maintaining anammox bacteria (AnAOB), which have a relatively low growth rate. This study aimed to evaluate the formation, stability, and granulation of anammox sludge in systems fed with real wastewater from the anaerobic digestion of pig waste by investigating the impact of (a) nitrite supplementation and (b) the role of microbiological consortia on a bench and pilot scale. The results showed that the bench- scale Anammox system had an average nitrogen removal efficiency of 85%, with a maximum ammonia nitrogen consumption (ANC) capacity of 2.32 kgN m-³ d-¹. In contrast, the deammonification system performed better, with a maximum ANC of 5.79 kg N m-³ d-¹ and a nitrogen removal efficiency (NRE) of 82%. Analysis of the extracellular polymeric substances (EPS) revealed that the ratio of proteins to polysaccharides (PN/PS) was fundamental to stability, as well as the formation of granules and biofilms, being more stable in the deammonification system, which showed greater resilience to load variations. On a pilot scale, the Anammox system achieved 72% NRE and 2.66 ± 0.27 kg N m-³ d-¹ of ANC. This study confirmed the hypothesis that anammox consortia (AnAOB and AOB) contribute to greater process resilience to load variations, promoting more stable performance in the long term. In addition, nitrite supplementation effectively maintained the Anammox process, although microbiological consortia were crucial for obtaining better results, as in the deammonification system. The formation of anammox granules and the system's stability are directly related to the quantity and composition of the extracellular polymeric substances excreted, which contribute to the mechanical resistance of the granules and biofilms.